SYNOVIAL MEMBRANE CHANGES IN PATIENTS WITH RHEUMATOID ARTHRITIS REVEALED DURING ARTHROSCOPY - E. B. Komarova (Научно-практическая ревматология)
Exudative or proliferative processes accompanied by joint destruction may predominate in the synovial membrane (SM) in different stages of rheumatoid arthritis (RA). The features of SM changes should be considered in the early diagnosis of RA and in the development of combination treatment for this disease.Objective: to study arthroscopic SM changes in patients with different RA durations and different blood anti-cyclic citrullinated peptide (anti-CCP) antibody levels.Subjects and methods. 37 patients with RA underwent arthroscopy with an arthroscope of a 2.4-mm diameter and 30° angle (Karl Storz GmbH, Germany). RA duration was <2 years in 17 patients and ranged from 2 to 8 years in 20; the blood level of anti-CCP antibodies did not exceed 60 IU/ml in 15 patients and it was higher in 22. SM changes were assessed by a semiquantitative method.Results and discussion. Arthroscopy revealed a preponderance of SM hyperemia with an increased vascular pattern (p<0.01) and fibrin deposits (p<0.05) in patients with a RA duration of < 2 years and that of villous hyperplasia with the formation of club-shaped villi (p<0.05) in those with a RA duration of >2 years. The increase in anti-CCP by >60 U/ml was associated with a predominance of inflammatory hyperplasia (p < 0.01), SM hyperemia with a pronounced vascular pattern (p<0.05), as well as with the presence of pannus (pp<0.01).